Clinical and molecular epidemiological study of xeroderma pigmentosum in China: A case series of 19 patients. Issue 1 (8th September 2016) - Zhou, Eray Yihui; Wang, Huijun; Lin, Zhimiao; Xu, Guiwen; Ma, Zhihong; Zhao, Jiahui; Feng, Cheng; Duo, Lina; Yin, Jinghua; Yang, Yong
Abstract: Xeroderma pigmentosum (XP) is a rare genetic disorder which is divided into eight complementation groups: XP‐A to XP‐G and XP‐V. Some XP patients demonstrate severe cutaneous and neurological manifestations, management of which requires timely diagnosis and intervention. We performed clinical evaluation and genetic analysis on 19 patients, the largest cohort of XP to date in China. Twenty‐three mutations from six groups were identified, 16 of which were novel. All patients developed marked freckle‐like pigmentation on sun‐exposed sites while patients with XP‐A, XP‐D, XP‐F and XP‐G showed acute sunburn reactions. Only XP‐A patients displayed progressive neurological degeneration. A relatively larger proportion of XP‐A and XP‐C were found in Chinese XP patients. One XP case and two carriers were prenatally determined. This study extended the mutation spectrum of XP in China and may aid in the diagnosis and treatment of Chinese XP patients.